Investigation of aerodynamic noise reduction of exterior side view mirror based on bionic shark fin structure. (November 2021) - Ye, Jia; Xu, Ming; Xing, Peng; Cheng, Yi; Meng, Dongxiao; Tang, Yulin; Zhu, Maotao
Abstract: The LES (Large Eddy Simulation) model based on different subgrid-scale models was used to calculate the aerodynamic noise of the side view mirror. The simulation result of Algebraic Wall-Modeled LES Model (WMLES) in LES was proved to be more accurate through the wind tunnel test. In order to explore the noise reduction mechanism of bionic shark fin, the shape of shark fin was studied and applied to the shell of side view mirror. The simulation results indicated that the bionic shark fin structure could effectively comb the streamline of the side view mirror surface and reduce the negative pressure area. The turbulence intensity at the rear of the side view mirror was reduced, which was beneficial to reduce the aerodynamic noise of the side view mirror on the front side window area. The maximum noise reduction could reach 7.3 dB.